Vascular Kv7 channels control intracellular Ca2+ dynamics in smooth muscle. (December 2020) - Tsai, Yuan-Ming; Jones, Frederick; Mullen, Pierce; Porter, Karen E.; Steele, Derek; Peers, Chris; Gamper, Nikita
Graphical abstract: Highlights: Inhibition of Kv7 channels induce Ca 2+ signals through L- and T-type VGCCs in rat and human vascular smooth muscle cells. Kv7.5 is functionally the most important subunit to mediate these effects. Phospholipase C mediated Kv7 inhibition is likely to contribute to Ca 2+ oscillations induced in VSMCs by vasopressin. Kv7 activator, retigabine, strongly suppresses [Ca 2+ ]i oscillations induced by vasopressin or direct Kv7 channel inhibition. Abstract: Voltage-gated Kv7 (or KCNQ) channels control activity of excitable cells, including vascular smooth muscle cells (VSMCs), by setting their resting membrane potential and controlling other excitability parameters. Excitation-contraction coupling in muscle cells is mediated by Ca 2+ but until now, the exact role of Kv7 channels in cytosolic Ca 2+ dynamics in VSMCs has not been fully elucidated. We utilised microfluorimetry to investigate the impact of Kv7 channel activity on intracellular Ca 2+ levels and electrical activity of rat A7r5 VSMCs and primary human internal mammary artery (IMA) SMCs. Both, direct (XE991) and G protein coupled receptor mediated (vasopressin, AVP) Kv7 channel inhibition induced robust Ca 2+ oscillations, which were significantly reduced in the presence of Kv7 channel activator, retigabine, L-type Ca 2+ channel inhibitor, nifedipine, or T-type Ca 2+ channel inhibitor, NNC 55-0396, in A7r5 cells. Membrane potential measured using FluoVolt exhibited a slow depolarisation followed by a burst of sharp spikes in response to XE991; spikes were temporally correlated with Ca 2+ oscillations. Phospholipase C inhibitor (edelfosine) reduced AVP-induced, but not XE991-induced Ca 2+ oscillations. AVP and XE991 induced a large increase of [Ca 2+ ]i in human IMA, which was also attenuated with retigabine, nifedipine and NNC 55-0396. RT-PCR, immunohistochemistry and electrophysiology suggested that Kv7.5 was the predominant Kv7 subunit in both rat and human arterial SMCs; CACNA1C (Cav1.2; L-type) and CACNA1 G (Cav3.1; T-type) were the most abundant voltage-gated Ca 2+ channel gene transcripts in both types of VSMCs. This study establishes Kv7 channels as key regulators of Ca 2+ signalling in VSMCs with Kv7.5 playing a dominant role.